2012
DOI: 10.1371/journal.pone.0029602
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus and Network Dynamics Collide in a Ratiometric Model of the Antennal Lobe Macroglomerular Complex

Abstract: Time is considered to be an important encoding dimension in olfaction, as neural populations generate odour-specific spatiotemporal responses to constant stimuli. However, during pheromone mediated anemotactic search insects must discriminate specific ratios of blend components from rapidly time varying input. The dynamics intrinsic to olfactory processing and those of naturalistic stimuli can therefore potentially collide, thereby confounding ratiometric information. In this paper we use a computational model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Individual neuron dynamics of LNs and PNs were modeled using a first-order differential equation (Chong et al, 2012) that described the evolution of the firing-rate activation variable of a neuron over time: τdaidt=ai(t)+S(j  Pwi,jaj(t)+k  Lwi,kak(t)+d  Rvi,drd) with S(x)=x3/(0.53+x3) for x0, and S(x)=0 for x<0,…”
Section: Methodsmentioning
confidence: 99%
“…Individual neuron dynamics of LNs and PNs were modeled using a first-order differential equation (Chong et al, 2012) that described the evolution of the firing-rate activation variable of a neuron over time: τdaidt=ai(t)+S(j  Pwi,jaj(t)+k  Lwi,kak(t)+d  Rvi,drd) with S(x)=x3/(0.53+x3) for x0, and S(x)=0 for x<0,…”
Section: Methodsmentioning
confidence: 99%
“…For FPA dynamics, the network encoded ratios through the spatial identity of neurons, whereas LCA networks produced a PN output continuously varying in time (bottom panels in Figure 4). While both operating regimes were able to encode the pheromone ratio reliably, we observed in previous work (Chong et al, 2012) that the ratio encoding was faster and more accurate using LCA dynamics (see Discussion). Timing simulations of the MGC design were conducted in ModelSim (Mentor Graphics, USA) and showed complex spatiotemporal dynamics in both PN and LN cell equivalent to those found in the continuous version of the model.…”
Section: Resultsmentioning
confidence: 50%
“…To perform ratiometric processing of real-time chemosensor input we first developed a biologically-constrained computational model of the early stages of ratiometric processing in insects, the MGC of the AL, in Matlab (delete first) (Mathworks, USA) using probabilistic connectivity patterns based on morphological studies of the moth brain (Akers and O'Connell, 1991; Hansson et al, 1992; Sun et al, 1997; Hansson and Anton, 2000; Carlsson and Hansson, 2002; Carlsson et al, 2002)—shown in schematic form in Figure 1A and described in detail in (Chong et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We model the network by three vectors x,y, and truez, where each element in the vector represents a neuron and modeled by a firing-rate unit (Linster et al, 2005; Capurro et al, 2012; Chong et al, 2012). The three vectors correspond to the three anatomical groups RNs, PNs, and LNs, respectively:…”
Section: Methodsmentioning
confidence: 99%